2012
DOI: 10.1111/j.1528-1167.2012.03699.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired neurovascular coupling to ictal epileptic activity and spreading depolarization in a patient with subarachnoid hemorrhage: Possible link to blood–brain barrier dysfunction

Abstract: SUMMARY Spreading depolarization describes a sustained neuronal and astroglial depolarization with abrupt ion translocation between intraneuronal and extracellular space leading to a cytotoxic edema and silencing of spontaneous activity. Spreading depolarizations occur abundantly in acutely injured human brain and are assumed to facilitate neuronal death through toxic effects, increased metabolic demand, and inverse neurovascular coupling. Inverse coupling describes severe hypoperfusion in response to spreadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…This is suggested by another study by Woitzik et al which found evidence of delayed cerebral ischemia in aSAH patients with no angiographic evidence of vasospasm, but did experience CSDs (Woitzik et al, 2012). This inverted neurovascular coupling after aSAH has also been observed using laser Doppler flowmetry (LDF) during ictal epileptic activity (Winkler et al, 2012). While these studies provide insight into pathological neurovascular coupling in the acute period following an injury, the reliance on additional and unconventional monitoring modalities has limited the studies on human patients.…”
Section: Discussionmentioning
confidence: 69%
“…This is suggested by another study by Woitzik et al which found evidence of delayed cerebral ischemia in aSAH patients with no angiographic evidence of vasospasm, but did experience CSDs (Woitzik et al, 2012). This inverted neurovascular coupling after aSAH has also been observed using laser Doppler flowmetry (LDF) during ictal epileptic activity (Winkler et al, 2012). While these studies provide insight into pathological neurovascular coupling in the acute period following an injury, the reliance on additional and unconventional monitoring modalities has limited the studies on human patients.…”
Section: Discussionmentioning
confidence: 69%
“…It is believed that the blood-brain barrier is disrupted by this inciting insult, allowing for changes in extracellular concentrations of ions including a decrease in magnesium concentrations and elevation in potassium levels [7,8,9]. Such changes alter the local neuronal microenvironment and trigger a cascade of cellular events ultimately leading to glutamate-induced toxicity [10].…”
Section: Mechanism Of Csd and Vascular Responsementioning
confidence: 99%
“…Previous studies based on Monte Carlo simulations using similar optical probe tip designs have estimated the optical sampling depth to approximately 1 mm in brain tissue [16,9,18]. The probe design could also be compared with previous investigations where a subdural optode-strip was used on the brain surface [7,35]. As the LDPM system can be equipped with multiple detectors our configuration also allows for multipoint recordings, but with the added advantage of measurement possibilities inside the tissue.…”
Section: Discussionmentioning
confidence: 94%
“…Recently Dreier et al applied LDPM on the surface of the brain using an optode strip combined with electrodes to study spreading ischemia 2009 [7] and epileptic activity 2012 [35] in patients with subarachnoid haemorrhage. LDPM is, however, still not an established monitoring method in the neurosurgical and neurointensive care setting.…”
Section: Introductionmentioning
confidence: 99%